UI/UX Using Design Thinking Method in Clarient Hotel Application Design - Setiawan, Dimas; Dalhats, Muhammad Ragil Shafa Abdur Rafi (JISA(Jurnal Informatika dan Sains), 2025)
Clairent Hotel is an online hotel room booking application specifically targeting the Bali area. A crucial aspect of developing an effective application is designing the user interface (UI) and user experience (UX) to meet the needs of users. This is particularly important for delivering an optimal experience during both leisure and business trips in Bali. Clairent Hotel serves as a platform for hotel rental services. The development of the Clairent Hotel application employs the design thinking method, which consists of five research stages: empathize, define, ideate, prototype, and test. The outcome of this research is an application that operates smoothly with a user interface that is intuitive and easy to navigate.